Optimal location query on road networks - Mohamad Ridzuan Yusop (2015)
This report is based on the research paper Optimal Location Queries in Road Network Databases. Optimal Location Queries are useful for strategic planning of resources in spatial databases. For example, in a given road network which consist of vertices which are either part of the road network, an existing client or facility, a query can ask for a location to build a new facility that optimises a certain cost metric. 3 variants of OL queries together with several query-processing algorithms will be discussed in this report, which are Competitive, Min-Sum and Min-Max location queries. Competitive Location Query ask for a location which maximise the total weights of clients attracted, Min Sum ask for a location which minimise the total weighted attractor distance and Min Max ask for a location which minimise the maximum weighted attractor distance. The aim of this project is to implement and evaluate the efficiency of the queries in terms of runtime and memory consumption. The location queries will be evaluated using different parameters and edge traversing methods.